Development Of Web Database Application For Research And Consultancy Project Management - Norhaiza, Khairudin (2002)

(untitled)
Database system has evolved in the recent years. Good decisions nowadays, require good information that comes from a manageable data store. Data are likely to be managed most efficiently when they are stored in a database. The Internet has transformed database management system and put them in move towards the integrated Internet-enabled database application. Organisations are now rapidly building new database applications or reengineering existing ones to take full advantage of the web as a strategic platform in becoming Web-centric organizations. This report discusses the database system development and framework for developing a prototype system for Project Development Web Database System for the Center for Research and Consultancy, Universiti Utara Malaysia (CRC) that has been developed using MySQL, PHP and Apache. The system development was designed using the Database Life Cycle (DBLC) approach. Apart from that, this project report discusses the findings and issues and challenges encountered during the development of the web database system. This prototype system was successfully being developed together with a user manual designed as a guide for the system users. It is hoped that this prototype system will contribute as a model and used as a reference in the implementation of a Web Database System for the CRC. It is also hoped that the system prototype will be further developed and further enhanced by the CRC as well as other schools and departments in UUM or any project management units in all institutes of higher learning thoughout the country.